Association of single nucleotide polymorphisms in the microRNA miR‐1596 locus with residual feed intake in chickens. (27th March 2015) - Luo, C.; Sun, L.; Ma, J.; Wang, J.; Qu, H.; Shu, D.
Summary MicroRNAs are an abundant class of small non‐coding RNAs that regulate gene expression. Genetic variations in microRNA sequences may be associated with phenotype differences by influencing the expression of microRNAs and/or their targets. This study identified two single nucleotide polymorphisms (SNPs) in the genomic region of the microRNA miR‐1596 locus of chicken. Of the two SNPs, one was 95 bp upstream of miR‐1596 (g.5678784A>T) and the other was in the middle of the sequence producing the mature microRNA gga‐miR‐1596‐3p (g.5678944A>G). Genotypic distribution of the two SNPs had large differences among 12 chicken breeds (lines), especially between the fast‐growing commercial lines and the slow‐growing Chinese indigenous breeds for the g.5678784A>T SNP. Only the g.5678784A>T SNP was significantly associated with residual feed intake (RFI) in the F2 population derived from a fast‐growing and a slow‐growing broiler as well as in the pure Huiyang bearded chicken. The birds with the AA genotype of the g.5678784A>T SNP had lower RFI and higher expression of the mature gga‐miR‐1596‐3p microRNA of miR‐1596 than did those with the other genotypes of the same SNP. We also found that the expression of the mature gga‐miR‐1596‐3p microRNA of miR‐1596 was significantly associated with RFI. These findings suggest that miR‐1596 can become a candidate gene related to RFI, and its genetic variation may contribute to changes in RFI by altering expression levels of the mature gga‐miR‐1596‐3p microRNA in chicken.